An algebra of Soviet power elite circulation in the Belorussian Republic, 1966-86 - Urban, Michael E. 1947- (Cambridge University Press, 1989)
Control of office has long been regarded as the key element in understanding power and policy in the Soviet system. What, however, accounts for the control of office and how are individuals recruited into positions of power and responsibility? In An Algebra of Soviet Power, Michael Urban adopts a fresh approach and introduces into the field of political elite studies the sociological technique of vacancy chain analysis. This treats the movements of actors as sequences of complex inter-relations that are structured by the properties and powers of the personnel system rather than by the consequences of individual intentions or characteristics. This algebraic method is applied to a large body of career data of officials from the Soviet Republic of Belorussia for the period 1966–86. The author documents how, despite the formal systems of nomenklatura - central control over personnel placement - the flow of individuals through the hierarchy of offices in Belorussia has not been influenced by any coordinating policy issuing from Moscow or Minsk. Instead regionalism has played an important, and patronage the decisive, role in the system
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1966-1986; Politik; Elite (Social sciences) / Belarus; Social mobility / Belarus; Politische Elite; Elite; Belarus / Officials and employees; Belarus / Politics and government; Belarus